Transportation Barriers and Language Constraints: A Qualitative Study of International Tourist Challenges in Accessing Iconic Destinations in Hsinchu, Taiwan - Kurniawati Baene; Pranoto (Jurnal Penelitian, 2026)
Hsinchu, known as the Silicon Valley of Taiwan and the 'Windy City', presents a paradox: a globally significant technology hub that remains largely undiscovered by international tourists compared to Taipei and Kaohsiung. This study examines two dominant barriers that impede international tourists from independently exploring Hsinchu's iconic attractions—namely, the complexity of public transportation systems and the pervasive language constraints arising from Chinese-language dominance in public signage, ticketing systems, and service encounters. Employing an interpretive qualitative methodology, this research conducted in-depth semi-structured interviews with 24 international tourists from 14 countries who visited Hsinchu between August and November 2024. Data were analysed using Braun and Clarke's (2006) six-phase reflexive thematic analysis, yielding four overarching themes: (1) navigational disorientation in multi-modal transit systems; (2) communicative exclusion at transport interfaces; (3) cumulative anxiety and destination avoidance; and (4) adaptive coping strategies and technological mediation. The findings reveal that language barriers and transportation complexity function not as isolated inconveniences but as mutually reinforcing constraints that produce compounded tourist anxiety and significantly reduce destination reach, particularly for non-Chinese-speaking independent travellers. Theoretical and practical implications are discussed, with particular attention to destination marketing, smart tourism infrastructure, and multilingual accessibility frameworks. The study contributes to growing scholarship on under-researched secondary cities in East Asia and advances understanding of inclusive tourism development in language-complex destinations.